(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Introduction: Dental caries remains one of the most prevalent chronic oral diseases worldwide, driven primarily by the interplay between dietary sugars, oral microbial activity, and salivary pH. Chewing gum is widely consumed as a functional confectionery, yet its impact on salivary parameters depends largely on its composition. Sugar-free gums, particularly those containing xylitol, are reported to exert anti-cariogenic effects by stimulating salivary flow and inhibiting bacterial metabolism, while sugar-containing gums may promote acid production and microbial proliferation. Objective: This study aimed to compare the effects of sugar gum and sugar-free gum on salivary pH and microbial load among young adults, with the goal of assessing their potential roles in caries prevention. Method of Analysis: A randomized controlled experimental design was employed with 10 healthy participants aged 18–25 years, equally divided into sugar gum and sugar-free gum groups. Baseline saliva samples were collected after a 30-minute fasting period. Salivary pH was measured at baseline, 10 minutes, and 30 minutes post-chewing using calibrated pH strips, while microbial load was determined by pour plate analysis and expressed as colony-forming units per milliliter (CFU/mL). Data were analyzed using independent sample t-tests to compare pH changes and microbial counts between groups. Results: Sugar-free gum produced a steady rise in salivary pH from baseline acidic levels (pH 4–5) to neutral pH 7 within 30 minutes, accompanied by a marked reduction in microbial load. In contrast, sugar gum produced inconsistent pH changes, with transient spikes followed by declines to acidic levels, and significantly increased bacterial growth, with some samples rising from 2×10¹ to 20×10¹ CFU/mL over 30 minutes. Conclusion: Sugar-free gum, particularly xylitol-containing formulations, effectively neutralizes salivary acidity and suppresses cariogenic bacterial growth, supporting its role as a practical adjunct in caries prevention. Conversely, sugar gum fosters acidogenic conditions that favor microbial proliferation despite initial salivary stimulation. These findings underscore the importance of promoting sugar-free gum use through public health campaigns and consumer education to reduce caries risk.